If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(a + 1) = a + 13 Reorder the terms: 3(1 + a) = a + 13 (1 * 3 + a * 3) = a + 13 (3 + 3a) = a + 13 Reorder the terms: 3 + 3a = 13 + a Solving 3 + 3a = 13 + a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. 3 + 3a + -1a = 13 + a + -1a Combine like terms: 3a + -1a = 2a 3 + 2a = 13 + a + -1a Combine like terms: a + -1a = 0 3 + 2a = 13 + 0 3 + 2a = 13 Add '-3' to each side of the equation. 3 + -3 + 2a = 13 + -3 Combine like terms: 3 + -3 = 0 0 + 2a = 13 + -3 2a = 13 + -3 Combine like terms: 13 + -3 = 10 2a = 10 Divide each side by '2'. a = 5 Simplifying a = 5
| -1.32+4.5= | | 1.32+4.5= | | -0.08*9= | | 8t^2-100t-1000=0 | | 4m-3-2m= | | 3-2(-5-6k)=-83 | | 25x^2-144=o | | 17/13=x/4 | | 4381+.2x=x | | -20-1= | | (2x+6)+(-3x+8)= | | 9m(3n+m-6)= | | x/12-15=219 | | -11x+9(x+10)=12 | | x/12-15m=219 | | -0.72-0.6= | | 3+5(-4r-5)=-5r+23 | | y-0.11y= | | 20*9w=4(15-w) | | 5[3(x+4)-2(1-x)]-x-25=14x+45 | | 9/144 | | 55t+165=40t | | f(x)=7x+1 | | 6x-3+4=25 | | (3x^2+2x-2)-(x^2-3x+7)= | | 4(2x)-3=17x+15 | | X^2-36=16x | | -27=-3p+5-3p | | (.7d+1)(1.5d-2)=(2.5+d)(4-1.3d) | | 2x^4=e^6 | | 0=12x^2+5x-2 | | 500-25= |